(untitled) - Derek H.R Barton (Cambridge, New York, 1993)
The book explores the invention of new chemical reactions for use in synthesis of biologically and economically important compounds. It begins with a mechanistic study of the industrial inpoetance of the pyrolysis of chlorinated alkanes. It continues with a theory on the biosynthesis of phenolate radical coupling. Included in the book is a description of the work on nitrite photolysis which involved the invention of new radical chemistry leading to a simple synthesis of the hormone aldosterone
Keywords: free radical reactions,organic compounds - synthesis